2020
DOI: 10.1007/s10639-020-10383-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding emergent teaching and learning practices: iPad integration in Polish school

Abstract: The appearance of tablet technology in the classroom is considered an obvious modernisation milestone. In the last few years school professionals in Poland have made large investments in digitalisation, especially through one to one model (1:1), using digital devices such as tablets. Researches on tablet technology integration in school classrooms convince that digital technologies are closely related to the discourse of educational change. What really changes when digital technology is used in the classroom? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, the comments suggest students perceived the paper assignment as boring compared to doing the same assignments on a tablet, regardless of whether they were doing it in the 1:1 or in the 1:m distribution. It should be taken into consideration that tablets could have caused a wow effect because these students usually work with paper in school [41]. Hence, to deepen the understanding of the observed differences in perceived satisfaction, future investigations should replicate the research design of this study with students who are exposed to tablets more frequently and possibly without the paper condition included.…”
Section: B What Is the Students' Perceived Satisfaction With The 1:m ...mentioning
confidence: 98%
“…In addition, the comments suggest students perceived the paper assignment as boring compared to doing the same assignments on a tablet, regardless of whether they were doing it in the 1:1 or in the 1:m distribution. It should be taken into consideration that tablets could have caused a wow effect because these students usually work with paper in school [41]. Hence, to deepen the understanding of the observed differences in perceived satisfaction, future investigations should replicate the research design of this study with students who are exposed to tablets more frequently and possibly without the paper condition included.…”
Section: B What Is the Students' Perceived Satisfaction With The 1:m ...mentioning
confidence: 98%
“…The earlier research showed technology integration in didactical design implemented using iPad [17], [47], [50], [51], digital and tangible artefacts [52]. However, this integration technology requires special devices that must be owned by students and teachers.…”
Section: Designing Digital Module Using Digital Didactical Design (Ddd)mentioning
confidence: 99%
“… 2019 ). Although the e-learning systems kept changing their content structures (from traditional to multi-modal and customized) with time (Kempe and Grönlund 2019 ), they have always been favored due to their low-cost educational resources (Kopciewicz and Bougsiaa 2021 ; Nipa and Kermanshachi 2020 ). Even more, there has been no significant difference between the conventional classroom-based environment and self-study sessions supported by the e-learning paradigm as more and more users are getting along with this change (Leonard et al.…”
Section: Introductionmentioning
confidence: 99%